Correlações entre Doença Periodontal e Aterosclerótica Coronariana:presença de anticorpos Anti-Toxoplasma gondii em amostras de sangue, catéter e saliva humana. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The occurrence of oral diseases is related to habits, stress levels, diet and emotional factors. The oral cavity is the site of entry for many microorganisms and are manifested niche where the first symptoms of a number of diseases of systemic character. Periodontal disease (PD) is a chronic infectiousinflammatory that affects the supporting tissues of the teeth and support, and toxoplasmosis, a protozoonosis worldwide distribution, caused by an intracellular parasite Toxoplasma gondii, which infects 50% of the world population and has its transmission by feeding undercooked meats. The aim of this study was to assess the degree of impairment of periodontal diseases in humans checking the correlation with toxoplasmosis and Coronary Artery Disease (CAD). Sixty-four patients underwent coronary angiography and were divided into two groups: patients with CAD (n = 47) and patients without CAD (n = 17). The results of angiography of patients with / without CAD demonstrated that the category of coronary obstructive lesions between 25% and 50% and> 50% the number of injuries among experimental groups in the right coronary artery, anterior and circumflex were statistically different (p = 0.0001) concluding that atherosclerosis can cause lesions in various arteries varying degree at the same time. The number of patients with hyperglycemia in the group with coronary disease, caused by stress hyperglycemia during hospitalization of patients with acute myocardial infarction without history of diabetes, show a higher rate of glycemic alterations in these patients (48.9%). Patients with /without CAD, have also been analyzed qualitatively for the presence or absence of IgG, IgM and IgA anti-toxoplasma in serum, saliva and blood samples collected during angiography catheter. Although they are not statistically different among the experimental groups, the rates of absorbance in serum (p =0,476) and saliva (p = 0.7632) were higher for patients without CAD, indicating that the presence of antibodies to Toxoplasma gondii is higher in patients without CAD than in patients with CAD. Regarding the parameters of periodontal health the number of patients with bleeding sites and the number of bleeding sites was higher in patients with CAD (p = 0.0491 and p = 0.002, respectively), with the average number of sites with exudate higher in the group with no difference DAC (p = 0.6052) and number of missing teeth larger than in the group without CAD (p = 0.0001), suggesting a correlation between the parameters of oral and periodontal health with coronary atherosclerosis. The results suggest the correlation of oral problems systemic conditions with high prevalence in the population in case of toxoplasmosis and coronary atherosclerosis.
Correlations between Periodontal Disease and Coronary Artery: presence of anti-Toxoplasma gondii antibodies in blood samples, catheter and human saliva
Keywords: Periodontite; Aterosclerose e Toxoplasmose; Periodontitis; Atherosclerosis and toxoplasmosis; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA